Analysis of Methanol Yellow in Yellow Food Circulating in the Jambi City Market - Yuli Hidayati; Yulianis Yulianis; Medi Andriani (Jurnal KESANS : Kesehatan dan Sains, 2022)
Introduction: Metanil yellow is a synthetic dye commonly used in the textile, paper, paint industry, but is sometimes misused as a food coloring. The misuse of methanil yellow coloring includes noodles, crackers and snacks and tofu which has a striking yellow color. Research Objectives: To determine the presence of Methanyl Yellow dye in yellow food circulating in Angso Duo. Research Methods: By using the identification of Color Reaction, Thin Layer Chromatography (TLC) and UV-VIS Spectrophotometry. Research Results: Based on the results of research conducted on 9 yellow food samples circulating in the Angso Duo market using the Color Reaction method, Simple Application, Thin Layer Chromatography (TLC) and UV-Vis Spectrophotometry showed negative results (-). Conclusion: In this study, it can be concluded that the 9 food samples did not identify any prohibited dyes, namely methanyl yellow and free from the colorant content of methanyl yellow.